Improved outcome with combined US/CT guidance as compared to US guidance in percutaneous radiofrequency ablation of small renal masses. (December 2015) - Andersson, Mats; Hashimi, Farida; Lyrdal, David; Lundstam, Sven; Hellström, Mikael
Background: When performing percutaneous radiofrequency ablation (RFA) of small renal masses (SRM), use of optimized periprocedural image guidance is essential to secure curative outcome of the treatment. Purpose: To retrospectively compare the short-term radiological and clinical outcomes of RFA under combined ultrasound (US) and computed tomography (CT) guidance with that of a previously performed US-guided series at the same institution. Material and Methods: From November 2009 to November 2013, 60 patients (mean age, 70.1 years; range, 34–86 years) with renal masses measuring in the range of 13–50 mm in maximal diameter (mean diameter, 25.4 ± 6.8 mm) underwent percutaneous RFA with combined US/CT guidance. The technical success rate, recurrence-free survival, rate of complications, and the percentage change in the estimated glomerular filtration rate (eGFR) were compared with that of a previously published series of 41 patients with SRM treated with US-guided RFA between November 2002 and December 2008. Results: The tumor and patient characteristics were similar between the two treatment groups. The primary and secondary technical success rate was significantly higher in the group treated with combined US/CT guidance compared with the group treated with US guidance alone (100% and 100% vs. 82% and 91%, respectively). The local recurrence-free survival was significantly better in the combined US/CT-guided group than in the US-guided group ( P = 0.016). There was no significant difference in the rate of overall complications (13% vs. 17%) or the mean percentage decrease in the eGFR after the respective treatment (1.1 ± 18.3% vs. 5.0 ± 11.7%). Conclusion: The use of combined US/CT guidance when performing renal RFA resulted in superior primary and short-term outcome compared to the use of US guidance alone in patients treated at the same institution.